Codon 72 polymorphism of p53 in Israeli Jewish cervical cancer patients and healthy women. Issue 6 (1st October 2002) - Arbel-Alon, S.; Menczer, J.; Feldman, N.; Glezerman, M.; Yeremin, L.; Friedman, E.
Abstract : Recently it has been found that the presence of homozygous arginine polymorphism at codon 72 of p53, represents a significant risk factor in the development of HPV-associated cervical cancer. The incidence of cervical carcinoma is persistently very low in Israeli Jewish women for unknown reasons. The incidence among those of North African origin is relatively higher. The aim of the present study was to assess the frequency distribution of the p53 homozygous arginine polymorphism in cervical cancer patients and in a population sample of healthy Israeli Jewish women in order to determine whether the incidence pattern among them is genetically based. The cases consisted of 23 Israeli Jewish patients with histologically confirmed squamous cell carcinoma of the cervix. A group of 162 randomly chosen Israeli Jewish healthy participants, considered to represent the general population, comprised the controls. The germline p53 polymorphism at codon 72 was determined by PCR in DNA obtained from a blood sample taken from each subject. Homozygous arginine was found in 34.8% of cases and in only 14.8% of controls. This difference was statistically significant ( P = 0.01). The frequency of homozygous arginine polymorphism in controls was lower than in any other population hitherto reported. It was significantly more common among those of North African than among those of other origin (30.3% vs. 10.8%; P < 0.01). It may be assumed that the low incidence of cervical cancer in Israeli Jewish women and the differences between the ethnic groups may be related to the frequency pattern of the homozygous arginine p53 polymorphism